On the application of models of the semantic space of music in the integrative analysis of musical works and music education with music computer technologies - Gorbunova, Irina Borisovna (2020)
In the second half of the 20th century, many music researchers demonstrated a steady interest in music categories as the space and time, whose fundamental nature and unifying (integrating) potential are obvious. However, despite the undoubted contribution to the consolidation of the findings, there was a need for further improvement in music studies, both regarding the content and the logical (including mathematical) research apparatus. This article considers these aspects of the comprehensive model of the semantic space of music in modern research theory and practice and its impact on the system of contemporary musical education.